Export of organic panela - CEPRESA Associtation - Martínez Sandoval, Katherine del Milagro (2018)
The objective of this research was to: Identify new markets for the export of organic panela from the CEPRESA association. For this, a market study was carried out according to the ITC methodology to be able to diversify the potential markets to export organic granulated panela. In order to obtain the information, three populations have been taken into account, which are the following: workers of the CEPRESA Association (Association objective of the study), experts in international commerce and business: Lic. Richard Montes Tocto and Lic. Carlos Ypanaque Estrada, and finally an exporting company of organic panela: Cooperativa Norandino, to whom interviews were applied. According to the results it was concluded that the association must improve in the production process looking for a new innovative process to be able to produce an even more profitable and attractive product for the final consumption, with respect to the potential markets are Europe and Asia that have a consumer with a demanding profile in terms of quality, loyalty program, price, are more informed at the time of consumption, are sensitive to brands; and with the third aspect the target market that launched this research was New Zealand which has as influential factors for the importation of "organic" products the following: Tariff preference Peru - New Zealand, foods imported as "organic" must comply with the standards from the Ministry of Premium Industries, the food standards code of Australia and New Zealand, and any other legislation made under the food law.